Does air pollution affect executive pay? - Liguang Zhang; Liao Peng; Kang He (China Journal of Accounting Studies, 2021)
Senior talents are the source and driving force of sustained economic growth, so attracting and retaining senior talents is crucial to local economic development. From the perspective of senior talents – executives, using a sample of publicly traded A-share listed companies during 2005–2018 in China, we examine the impact of air pollution on executive compensation. We find that air pollution level is significantly and positively correlated with executive compensation. This effect is more prominent for firms have less bargaining power, firms where executives have more bargaining power and executives are younger. Further studies show that air pollution inhibits the accumulation of local executive talent. Finally, adjusting executive compensation according to air pollution levels can improve future firm performance. All in all, from the perspective of listed firms’ decision makers, this paper enriches and expands the literature about economic outcomes of air pollution and further reveals the micro mechanism of air pollution negatively influencing macro economic development, providing the empirical evidence for local government policy making of talent introduction, improving the environmental governance capacity and finally promoting high quality economic development.